(untitled) (Bangladesh Pharmaceutical Journal, 2024)
This current research work was conducted an investigation into the biological activities of various fractions of Byttneria pilosa Roxb. (Family: Sterculiaceae) and analyze the chemical compositions. Preliminary examination of the raw fractional extractives identified the presence of alkaloids, glycosides, flavonoids, saponins, reducing sugars, and tannins. The standard was acetyl salicylic acid for heat-induced method to evaluate the anti-inflammatory and membrane-stabilizing properties. The crude ethanol extract displayed a moderate activity, inhibiting albumin denaturation by 44.7% compared to the positive control. All three extractives also demonstrated significant (p<0.05) in-vitro membrane-stabilizing activity. Additionally, the plant showcased robust antioxidant properties, as evidenced by the IC50 values of the ethanol extract, nhexane extract and chloroform extracts (5.3, 5.4, and 6.2 μg/ml, respectively), one the contrary, the acetyl salicylic acid as standard drug exhibited an IC50 value of 3.8 μg/ml. In summary, the outcomes of this investigation propose that this specific plant species holds promise for the discovery of novel natural bioactive compounds. Bangladesh Pharmaceutical Journal 27(1): 110-115, 2024 (January)